PERGESERAN SEKTOR EKONOMI DAN PENYERAPAN TENAGA KERJA DI JAWA TIMUR - M. Saleh; Sonny Sumarsono (Research Centre for Population, Indonesian Institute of Sciences, 2011)
Based on GDP data in every region in East Java Province, the economic potential difference can be detected, as well as potential sectors to be developed Thus the development of investment in the region may consider efficiency both in terms of finance, economic growth, as well as its impact on employment. This paper will describe the analysis of the economic sectors of potential in the region of East Java Province and its effect on the absorption of labor in the sector tersebut. Untuk determine the potential in each district/city used method of location quotient (lq) and the method and the shift-share analysis of regional specialization. The data used are secondary data time series of 2004 s.d. 2008, obtained from the Central and East Java Province, statistical district/city and other literature sources. Data analysis in this study include: Descriptive analysis, typology Klassen, Gravity Model, location quotients (/q), shiftshare analysis, and analysis of regional specialisation. Based on the analysis in terms of potential, economic growth and employment is the principal findings of this study was as follows: 1) sector growing potential in the region are agriculture, mining and quarrying sector and the finance, leasing and corporate services, 2) the value of the sector linkages potential is high (value 1) between the six districts with Probo/inggo are agriculture, while other potential sector linkages kabupaten/city low value (less than one); 3) the largest contributor to GDP changes in the value of East Java Province in 2004-2008 was Jember; Banyuwangi and Probo/inggo. 4) The absorption of labor in the district is the largest agricultural sector, while in urban areas are the sectors of commerce and services. Sectors that have a major impact on employment differ across regions. Largest proportion of employment in the district are agriculture (over 70%) is in the district of Sam pang, Pacitan, and Pamekasan. While the proportion of energy absorption is greatest in urban areas by trade, restaurants and hotels mainly in the city of Madison, Surabaya and Blitar, and for the services sector is the City of Madiun, Blitar and Malang. Region with the highest proportion of employment in the industrial sector is Sidoharjo, Pasuruan and Gresik Regency. Based on the above-mentioned main findings, local goven1ments in East Java can find the potential sectors in the region, so that economic development can be done as efficiently as possible through a concrete program for the short, medium and long term, so as to reduce economic disparities between regions and increase the chance work in their respective areasKeyword: PDRB, potential sector, economic growth, labor absorption in East Java